TINJAUAN HUKUM PEMBENTUKAN PROVINSI PAPUA BARAT DAYA BERDASARKAN UNDANG-UNDANG NOMOR 23 TAHUN 2014 - Kondologit, Ehud Eduard; Murary, Weron; Baho, Dayen (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
The purpose of this study is to review the legal review of the formation of Southwest Papua Province based on Law Number 23 of 2014 concerning Regional Government, and the legal impact of the formation of Southwest Papua Province based on Law Number 23 of 2014 concerning Regional Government, through Law Number 29 of 2022 concerning the Establishment of Southwest Papua Province, becoming the 38th Province in Indonesia, this is a representation of government provisions contained in Law Number 23 of 2014 concerning Regional Government.This type of research uses normative legal research, focusing on research on written regulations or legislation or research based on rules or norms that apply in society. Secondary data is used by the author regarding primary legal materials in the form of literature/books related to the legal study of the formation of Southwest Papua Province, data analysis is used to analyze destructive and qualitative methods, by explaining in detail and precisely certain phenomena related to the writing of this law.From the results of the research, it was found that the expansion procedure has changed with the promulgation of Law Number 23 of 2014 which only specifies 2 requirements, namely basic requirements and administrative requirements. In addition, Law Number 23 of 2014 also stipulates that if an area is to be expanded, then the area must go through the preparatory regional stage. Southwest Papua Province is based on Law Number 29 of 2022, its territory includes Sorong Regency, South Sorong Regency, Raja Ampat Regency, Tambrauw Regency, Maybrat Regency, and Sorong City. The province is given special autonomy within the framework of the Unitary State of the Republic of Indonesia, which means that there are policies and regulations that are different from other provinces, which can affect the community and the local government. Keywords: Review, Law No. 23 of 2014, Formation, Southwest Papua